Sham rock [large type] - McInerny, Ralph, 1929-2010 (Notre Dame series, 2010)
"The University of Notre Dame relies on Roger Knight, the rotund professor of Catholic Studies, and his brother Philip, a semi-retired PI, to investigate delicate situations that could put the school in a bad light. Now a Notre Dame classmate has confessed to the decades-old murder and secret burial of one of his cloest friends. Ready to help the school put the sordid tragedy behind them, Roger and Philip set about the sad task of unearthing the victim's body -- only to find that they have a much bigger mystery with which to contend" --Back cover.